Progressivism : the strange history of a radical idea - Watson, Bradley C. S., 1961- (University of Notre Dame Press, 2020)
"Bradley C.S. Watson has devoted a significant part of his career to studying the nature of American progressivism as it formed in the twentieth century, and this book represents his synthesis of the history of this idea. In Progressivism: The Strange History of a Radical Idea, Watson presents an intellectual history of American progressivism as a philosophical-political phenomenon, focusing on how and with what consequences the academic discipline of history came to accept and propagate it. This book offers a meticulously detailed historiography and critique of the insularity and biases of academic culture. It shows how the first scholarly interpreters of progressivism were, in large measure, also its intellectual architects, and later interpreters were in deep sympathy with their premises and conclusions. Too many scholarly treatments of the progressive synthesis were products of it, or at least were insufficiently mindful of two central facts: the hostility of progressive theory to the Founders' Constitution and the tension between progressive theory and the realm of the private, including even conscience itself. The constitutional and religious dimensions of progressive thought-and in particular the relationship between the two-in effect remained hidden for much of the twentieth century. This pathbreaking volume reveals how and why this scholarly obfuscation occurred. The book will interest students and scholars of American political thought, the Progressive Era, and historiography, and it will be a useful reference work for anyone in history, law, and political science."--